(untitled) (American Journal of Islam and Society, 2010)
Is interfaith dialogue full of challenges or opportunities? Does it lead somewhere, or is it a never ending circular road? When we dialogue, do we still harbor the notion of converting our dialogue partners? Analyzing some of the actual work done by governments and non-governmental organizations (NGOs), as well as academics and individuals, may answer these questions. In this short article, I will focus on several efforts’ goals, success rate, and what we can learn from their experiences.